Improving the livelihood of small farmers in the pig value chain: Experiences in the north of Vietnam - Pham Van Hung; Nguyen Thi Duong Nga; Lapar, Ma. Lucila (Vietnam National University of Agriculture, 2015)
Livestock sector in general and pig production in particular are important in Vietnam not only for supplying food for its growing population but also for their significant contributions to the country’s economy. Smallholder pig producers which are common, are estimated to supply at least 80% of pork in total pork production in the country. The paper airms to draw a picture of pig production performance of small farmers based on the survey data of ILRI-VNUA and value chain approach. It is believed that pig smallholders in Vietnam perform a weak market orientation, and they do not have full information about market. Therefore, some implications should be as small pig farmers need facilitation from the government and training & improving veterinary network are needed; Government management on input and output markets should be strengthened effectively; The private sector should participate actively in the chains; and Awareness of food safety of people should be improved.